Large Eddy simulation of a heaving wing on the Cusp of transition to turbulence. (30th April 2019) - Badoe, Charles E.; Xie, Zheng-Tong; Sandham, Neil D.
Highlights: Dynamic stall of a heaving wing is simulated in high resolution using large-eddy simulation. The validation of large-eddy simulation against the water tunnel experiments is successful. Flow instabilities at the leading edge are associated with the separation bubble transition. The spanwise perturbation in the reverse flow on the wing suction surface give rise to instabilities in the detached shear layer. The detachment of vortex tends to decrease the lift and increase the pitching moment. Abstract: Simulations of the flow over a heaving NACA 0012 wing are conducted to study the separated flow phenomena for a pre-stall and post-stall wing condition. An extensively validated high fidelity large-eddy simulation (LES) approach is used to examine the unsteady aerodynamic loads and flow structures at Reynolds number Rec = 2 × 10 4 based on the chord. We consider reduced frequencies of k = 0.47 and 0.94 for a chord-normalized peak-to-peak amplitude of A / c =0.5 and angles of attack of 5 ∘ and 15 ∘, representing pre-stall and post-stall conditions respectively. Comparison to experiment shows good agreement for the phase-averaged lift, drag and moments of the heaving wing. Characteristic phenomena of dynamic stall are analysed with emphasis on the leading edge vortex (LEV) development. A series of instantaneous spanwise vorticity plots show significant spanwise perturbations in the reverse flow region that develops over the suction surface during the start of the downstroke, giving rise to instabilities in the detached shear layer. The instabilities give rise to the first occurrence of turbulence near the wing surface at the leading edge.